Achados bucais e laboratoriais em pacientes com lúpus eritematoso sistêmico - Umbelino Júnior, Antonio Augusto (2008)
Systemic lupus erythematosus (SLE) is a chronic inflammatory disease with variable frequency between 5.0%-25.0% of oral manifestations. These manifestations are characterized by chronic ulcers or erythema, of variable dimensions, with periods of exacerbation and remission. The few studies about oral lesion in patients with SLE present in the literature revealed microscopically, para or ortokeratosis, acanthosis, epithelial atrophy, vacuolar degeneration of basal layer with necrosis of basal keratinocytes, thickening of basal layer, mononuclear lichenoid infiltrate and vasculitis in the connective deep tissues. There are observed high levels of circulating autoantibodies, mainly anti-nuclear antibodies, being the presence of them one of criterion suggested by American College of Rheumatology (ACR). Thus, our objective was to investigate the oral (soft and hard tissues) and laboratorial findings in patients with SLE. One hundred fifty-five patients with SLE diagnosis in accordance with ACR criterion were analyzed. The index of decayed, missed and filled teeth (DMFT) was registered and, after, the necessity of periodontal treatment was evaluated by Community Periodontal Index (CPI). Thus, we performed biopsies in all lesions diagnosed and smears of the lateral right and left borders of the tongue to citopathologic exams. Of 155 patients, 94.1% (145/155) were women and 5.9% (10/155) men. Elevated titles of circulating autoantibodies (ANA-Hep2) were observed in all patients, being 41.9% positive for anti-DNAds antibodies. In accordance with CPI, 9.0% (14/155) presented healthy gum, 18.8% (29/155) bleeding, 40.0% (62/155) calculus, 18.0% (28/155) pockets of 4-5 mm, 5.9% (9/155) pockets of 6mm or more and 8.3% (13/155) were excluded due to the total teeth absence. DMFT index mean of total sample was 18.5. Thirteen lesions were observed in 10 (6.5%) patients, but only eight oral lesions were biopsed from seven patients. The main affected sites were dorsum of the tongue, buccal mucosa and lips. The histopathologic exams demonstrated unspecific alterations, with epithelial hyperplasia associated with accentuated lamina propria edema and unspecific mucositis that could be associated to SLE manifestations. In others cases we observed epithelial hyperplasia with hiperkeratosis, focal and superficial areas of microabscess than can be compatible with benign migratory glossitis; benign migratory glossitis; lipoma and candidiasis; erosion associated with vasculitis and chronic inflammation; and cheilitis by SLE and actinic cheilitis in the same patient. These three last cases (3/155; 2.0%) were considered compatible with clinic indication of SLE. The prevalence of candidiasis corresponded to 20.1% (23/110) and of oral hairy leucoplakia to 3.7% (4/110). These data suggest that patients with SLE presented low prevalence of oral lesions and poor periodontal conditions. Besides, the citopathology presented important in the diagnosis of infections associated to immunosuppression state, as candidiasis and oral hairy leucoplakia